Aspek Kultural “Bismillahirrahmânirrahim” dalam Keislaman Orang Buton: Kajian terhadap Kabanti Ajonga Inda Malusa - Rosdin, Ali (el Harakah: Jurnal Budaya Islam, 2014)
This study aimed at describing to what extent expression bismilllahirrahmânirrahim influenced Islamic lives of Buton people in the past. The object of the study is script kabanti Ajonga Inda Malusa as H. Abdul Ganiu’s work. The study focuses on understanding the meanings constructed in kabanti Ajonga Inda Malusa by looking at its relationship with cultural elements and historical background of Buton people. In understanding the phrase bismilllahirrahmânirrahim, it used hermeneutic method supported with the sociological theory of literature, that views literature as (1) a reflection of its supporting society, (2) a document that records cultural social reality and the bias of the reality of society in its time, and (3) other aspects related to a society in accordance with conventions and historical background in its cultural social framework. The results showed that the statement bismilllahirrahmânirrahim is a tradition of Sufi poets in the past Buton Sultanate to start their work, which can be interpreted as a form of practice of Islamic refinement that always refers to the al Quran and Hadis. In the Islamic context of Buton people, the phrase bismilllahirrahmânirrahim then explored and elaborated into whole aspects of life, the world and the hereafter. Penelitian ini bertujuan untuk mendeskripsikan sejauhmana ungkapan bismilllahirrahmânirrahim berpengaruh dalam kehidupan keislaman orang Buton pada masa lampau. Objek kajiannya adalah naskah kabanti Ajonga Inda Malusa karya H. Abdul Ganiu. Kajian difokuskan pada pemahaman terhadap makna yang dibangun dalam kabanti Ajonga Inda Malusa dengan melihat hubungannya dengan unsur budaya dan latar belakang kesejarahan masyarakat Buton. Dalam memahami ungkapan bismilllahirrahmânirrahim, digunakan metode hermeneutik yang ditopang dengan teori sosiologi sastra, yang memperhatikan karya sastra sebagai (1) cermin masyarakat pendukungnya, (2) dokumen yang mencatat kenyataan sosial budaya serta bias dari realitas masyarakat pada masanya, dan (3) aspek-aspek lain yang berhubungan dengan masyarakat sesuai dengan konvensi dan latar belakang kesejarahan dalam kerangka sosial budayanya. Hasil penelitian menunjukkan bahwa pernyataan bismilllahirrahmânirrahim merupakan tradisi para penyair sufi di Kesultanan Buton masa lampau dalam mengawali setiap karyanya, yang dapat dimaknai sebagai wujud pengamalan adab Islam, yang senantiasa merujuk pada al Quran dan al Hadits. Dalam konteks keislaman orang Buton, pernyataan bismilllahirrahmânirrahim kemudian digali dan dijabarkan dalam seluruh aspek kehidupannya, dunia dan akhirat.